Tissue Plasminogen Activator and MRI Signs of Cerebral Small Vessel Disease - Larisa A. Dobrynina; Alla A. Shabalina; Maryam R. Zabitova; Elena I. Kremneva; Zukhra Sh. Gadzhieva; Marina V. Krotenkova; Elena V. Gnedovskaya; Alexander B. Berdalin; Lyudmila A. Kalashnikova (Brain Sciences, 2019)
Cerebral small vessel disease (SVD) is one of the leading causes of cognitive impairment and stroke. The importance of endothelial dysfunction and high blood−brain barrier (BBB) permeability in pathogenesis, together with ischemia, is under discussion. The aim of this study was to clarify the relationship between tissue plasminogen activator (t-PA), plasminogen activator inhibitor (PAI-1), and magnetic resonance imaging (MRI) signs of SVD. We examined 71 patients (23 men and 48 women; mean age: 60.5 ± 6.9 years) with clinical and MRI signs of SVD, and 21 healthy volunteers with normal MRIs. All subjects underwent 3T MRI and measurements of t-PA and PAI-1 levels. An increase in t-PA level is correlated with the volume of white matter hyperintensities (WMH) (R = 0.289, p = 0.034), severity on the Fazekas scale (p = 0.000), and with the size of subcortical (p = 0.002) and semiovale (p = 0.008) perivascular spaces. The PAI-1 level is not correlated with the t-PA level or MRI signs of SVD. The correlation between t-PA and the degree of WMH and perivascular spaces’ enlargement, without a correlation with PAI-1 and lacunes, is consistent with the importance of t-PA in BBB disruption and its role in causing brain damage in SVD.